Pengaruh Fasilitas Belajar Terhadap Minat Belajar Siswa SD Negeri Kutabima 01 - Utami, Maulidya; Riyadi, M. Ilham Rahmani; Azizah, Amalia Nurul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the influence of school facilities on student learning interest sd negeri kutabima 01. This research method used is a quantitative research method with survey research type. This research was carried out using survey research conducted using non-probability techniques where the researcher then collected data using a questionnaire. The data produced were analyzed using statistical tests, namely simple linear regression tests, namely the T test and determination coefficient (R square). This result of the research entitled the influence of school facilities on student learning interest sd negeri kutabima 01 had a siginificant effect. This can be seen from the average precentage after being given treatment on student’s learning interest, namely 0,019 (p < 0,05). The result of the coefficient of determintation test show that learning facilities explain 26,9% of the varioation in student motivation. This shows that although learning facilities are an important factor, there are other elements that also influence student motivation. However, the adjusted R Square value of 0.228 confirms that learning facilities still make a relevant contribution in this regression model, so this research that providing adequate learning facilities is very inportant in increasing student interest and motivation in the educational environment